5y-3+y+29=5y+30-1y

Simple and best practice solution for 5y-3+y+29=5y+30-1y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5y-3+y+29=5y+30-1y equation:


Simplifying
5y + -3 + y + 29 = 5y + 30 + -1y

Reorder the terms:
-3 + 29 + 5y + y = 5y + 30 + -1y

Combine like terms: -3 + 29 = 26
26 + 5y + y = 5y + 30 + -1y

Combine like terms: 5y + y = 6y
26 + 6y = 5y + 30 + -1y

Reorder the terms:
26 + 6y = 30 + 5y + -1y

Combine like terms: 5y + -1y = 4y
26 + 6y = 30 + 4y

Solving
26 + 6y = 30 + 4y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-4y' to each side of the equation.
26 + 6y + -4y = 30 + 4y + -4y

Combine like terms: 6y + -4y = 2y
26 + 2y = 30 + 4y + -4y

Combine like terms: 4y + -4y = 0
26 + 2y = 30 + 0
26 + 2y = 30

Add '-26' to each side of the equation.
26 + -26 + 2y = 30 + -26

Combine like terms: 26 + -26 = 0
0 + 2y = 30 + -26
2y = 30 + -26

Combine like terms: 30 + -26 = 4
2y = 4

Divide each side by '2'.
y = 2

Simplifying
y = 2

See similar equations:

| .6n-.6=6n+1.3 | | 3x+20=8x-40 | | 6g+18=9g-25 | | -7-7(4x+8)=-175 | | a-a^1/2-6=0 | | 3x+20=4x-5 | | a-a^1/2-6= | | 9r^2=18 | | g−3/7=2/7​​ | | 12-3(3-3x)=6x | | -235=.05(x)-.06(x) | | |x/2-3|-5-2 | | 3z/10-9=-8 | | 7a-1=4(3a+6) | | 14x-9=13x+51 | | 3/x-2=1/x | | 4/56 | | 3(4x+5y)=12 | | sqrt(x^2-3x)=2 | | -6+7(x-3)=37-x | | .08(x)+.12(x+250)=348 | | x+0.13x=3500 | | X^2-18x-31=0 | | 28=4/3w | | -7(-5k-8)=196 | | 24/0.3 | | 2f+3w=15.55 | | -272=3n-7(8n+1) | | 0.7z-3=0 | | 3.5+46.9*x-9.8*x^2=0 | | 6+3x=8+11 | | 1404=.02(x) |

Equations solver categories